Psychiatry and movies - Damjanović, Aleksandar, psihijatar (Array, 2009)
As one of the most potent and substantial form of mass communication, film exercises a very significant influence upon the perceptions of the audience, especially in relation to mental illness issues, and that perception is very much blurred with populists’ misinterpretation and lack of awareness regarding problems faced by persons suffering from mental disorders. Movies such as "Psycho", "One Flew Over Cuckoo’s Nest", "Exorcist", despite being valuable in an artistic sense, corroborated and encouraged confusion and undermined the clarity and certainty concerning the fine line separating mental health from mental illness. Modern film makers and movie theoreticians try to overcome these limitations which are often generated by exploitation of stereotypes and myths referring to mentally ill people